2018
DOI: 10.1159/000492260
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 Silencing in Ovarian Cancer Enhances the Chemotherapy Response

Abstract: Background/Aims: Cisplatin-based treatment is first-line chemotherapy for several cancers including ovarian cancer. The development of cisplatin resistance results in treatment failure, but the underlying mechanisms are not fully understood. Histone deacetylases (HDACs) are a large family of enzymes that deacetylate lysine residues on histones and non-histone proteins. High expression of HDAC1 is associated with poor outcomes in ovarian cancer. Furthermore, resistance to chemotherapeutic agents is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…The significant effects of lncRNAs in OV cells have been explored. For example, lncRNA HDAC1 silencing boosted the chemotherapy response in OV 20 . LncRNA HOTAIR facilitated motility and proliferation in OV via modulating PIK3P3 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The significant effects of lncRNAs in OV cells have been explored. For example, lncRNA HDAC1 silencing boosted the chemotherapy response in OV 20 . LncRNA HOTAIR facilitated motility and proliferation in OV via modulating PIK3P3 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The treatment that influenced the histone structure improved the efficacy of chemotherapy in tumors that had acquired drug resistance due to DNA methylation and gene silencing. Liu et al [94] also performed in vitro and in vivo studies. In cisplatin-resistant ovarian cancer cells, they showed that HDAC1 knockdown suppressed cell proliferation and increased apoptosis.…”
Section: Cisplatin Resistancementioning
confidence: 99%
“…21 promote the process of malignancy, and is associated with high recurrence, poor overall survival in the patients with ovarian cancer. 22 In the present study, we detected Wnt related genes, including β-catenin, LEF1, TCF7, c-MYC and cyclin D1 in overexpressed CK19 of SKOV3 cells, the results showed that the expression levels of the related genes were all increased. All these data demonstrated that overexpression of CK19 may activate the Wnt/β-catenin signaling pathway in SKOV3 cells.…”
Section: Discussionmentioning
confidence: 49%